Analysis of the Performance of RTV Silane Epoxy Resins as the High Voltage Polymeric Materials Insulator in Tropical Climate. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Silane epoxy resins are the name of new thermosetting polymeric insulation materials that have been developed, with the materials composition was obtained from the experimental research. Analysis of the performance of RTV silane epoxy resins is the multiple regression model, it is derived from statistical science combined with statistics toolbox from matlab programme. The observed performances from experimental methods as follow, flashover voltage, leakage current, equivalent salt deposit density, and contact angle of the hydrophobicity. For engineering proposed, it could be appied for silane epoxy resins to determine optimal performance the sample in tropical climate such as temperature, humidity, pressure, wind velocity, rain fall, and ultraviolet. The results of multiple regression model, it can be concluded that the silane treatment of the filler with the dose of 40 %, or specimen code of RTV24 gives optimal performance in the tropical climate. Therefore, these materials can be proposed as insulator materials for high voltage transmission line in tropical area, and as an alternative substitution for porcelain and glasses.